Seasonal variation and principle of cyanobacterial biomass and forms in the water source area of Chaohu City, China - 徐宪根 柯凡 李文朝 冯慕华 尚丽霞 范帆 何延召 (Chinese journal of oceanology and limnology, 2016)
We investigated seasonal variations in cyanobacterial biomass and the forms of its dominant population （M. aeruginosa） and their correlation with environmental factors in the water source area of Chaohu City, China from December 2011 to October 2012. The results show that species belonging to the phylum Cyanophyta occupied the maximum proportion of phytoplankton biomass, and that the dominant population in the water source area of Chaohu City was M. aeruginosa. The variation in cyanobacterial biomass from March to August 2012 was well fitted to the logistic growth model. The growth rate of cyanobacteria was the highest in June, and the biomass of cyanobacteria reached a maximum in August. From February to March 2012, the main form of M. aeruginosa was the single-cell form; M. aeruginosa colonies began to appear from April, and blooms appeared on the water surface in May. The maximum diameter of the colonies was recorded in July, and then gradually decreased from August. The diameter range ofM. aeruginosa colonies was 18.37-237.77μm, and most of the colonies were distributed in the range 20-200μm, comprising 95.5% of the total number of samples. Temperature and photosynthetically active radiation may be the most important factors that influenced the annual variation in M. aeruginosa biomass and forms. The suitable temperature for cyanobaeterial growth was in the range of 15-30℃. In natural water bodies, photosynthetically active radiation had a significant positive influence on the colonial diameter of M. aeruginosa （P〈0.01）.